Endoscopic papillectomy of benign ampullary lesions: Outcomes from a multicenter study - Attila, Tan; Parlak, Erkan; Alper, Emrah; Dişibeyaz, Selçuk; Çiçek, Bahattin; Ödemiş, Bülent (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Endoscopic papillectomy (EP) has emerged as an alternative to surgery in the management of ampullary lesions. The aim of this study is to evaluate feasibility, efficacy, safety, outcome, and impact of EP in the management of benign ampullary lesions. Materials and Methods: This is a multicenter, retrospective study of 44 patients who had EP of benign ampullary lesions. Results: Over the 11-year period, 44 (55.7%) of 79 patients underwent EP for benign ampullary lesions. Complete resection was achieved in 40 patients (91%). An underlying adenocarcinoma was the only risk factor for incomplete resection. Twenty-eight lesions (63.6%) were resected en-bloc and 16 lesions (36.4%) were resected in piecemeal fashion. Post-papillectomy histopathologic diagnoses were tubular adenoma in 14 patients (32%), invasive adenocarcinoma in 9 patients (20.5%), tubullovillous adenoma in 7 patients (16%), tubullovillous adenoma with carcinoma limited to the mucosal layer in 5 patients (11.3%), adenoma with high-grade dysplasia in 4 patients (9%), neuroendocrine tumor in 1 patient (2.3%), ganglioneuroma in 1 patient (2.3%), hamartomatous polyp in 1 patient (2.3%), adenofibroma in 1 patients (2.3%), and Brunner gland hyperplasia in 1 patient (2.3%). Seven (15.9%) procedure-related complications occurred: 3 (6.8%) with bleeding, 2 (4.5 %) with pancreatitis, 1 (2.3%) with abdominal pain, and 1 (2.3%) with stent migration to the pancreatic duct. Seven patients (17%) had recurrence. Conclusion: Endoscopic papillectomy is a safe and effective method and can be considered as a first-line approach in patients with benign ampullary lesions with intent for cure. It also allows for correct histological diagnosis and staging. Cite this article as: Attila T, Parlak E, Alper E, Dişibeyaz S, Çiçek B, Ödemiş B. Endoscopic papillectomy of benign ampullary lesions: Outcomes from a multicenter study. Turk J Gastroenterol 2018; 29: 325-34.